Bench-scale oil fouling/antifouling tests under high temperature and high pressure conditions and the underlying interfacial interaction mechanisms. (15th April 2022) - Qiao, Chenyu; Wang, Duo; Zhao, Ziqian; Yang, Wenshuai; Wu, Feiyi; Chen, Hongyun; Yin, Taiheng; Zhang, Ling; Liu, Qi; Yang, Dingzheng; Gao, Song; Zeng, Hongbo
Graphical abstract: Highlights: Novel method for antifouling test at high-temperature and high-pressure conditions. Effects of various factors on antifouling performance of a commercial antifoulant. Interaction mechanisms underlying fouling/antifouling phenomena in SAGD operation. Abstract: Oil fouling is commonly encountered in many environmental and engineering fields and remains a challenging issue. The fouling issue in steam-assisted gravity drainage (SAGD) process for extracting bitumen from oil sands deposits has received much attention from oil industry. In view of low capital investment and exceptional antifouling performance, adding antifoulants has emerged as a promising strategy for addressing fouling issues. Developing an efficient method to evaluate their antifouling performance under production conditions is urgently needed. In this work, we report a novel bench-scale test method for quantitatively evaluating the antifouling performance of antifoulants under high temperature and high pressure (HTHP), close to SAGD operation conditions. The effects of antifoulant dosage and stirring rate on the antifouling performance are systematically investigated. The underlying fouling and antifouling mechanisms are characterized through direct molecular and surface force measurements. It is found that the commercial antifoulant exhibits exceptional antifouling performance at the dosage range of 20–35 ppm, and increasing stirring rate enhances the antifouling behavior. The force measurement results indicate that the antifoulant can adsorb to organics and target substrate surfaces, performing the antifouling function by lowering the hydrophobic interaction between organics and target substrates. This work provides a novel and feasible method for characterizing fouling phenomena and evaluating antifoulants under HTHP conditions and improves the understanding of fundamental interaction mechanisms underlying the fouling and antifouling phenomena.